Effective Antifungal Compounds of Lactococcus lactic Against Vulvovaginal Candidiasis for Women in Thi-Qar Governorate - Haneen A. Alshadood,; Hadi, Iman (University of Thi-Qar Journal of Science, 2024)
One hundred and fifty-four samples were collected from Bint Al-Huda Teaching Hospital in Thi-Qar Governorate divided to 104 women infected urinary tract infection (UTI) and 50 healthy women as control group. Vulvovaginal Candidiasis (VVC) is the most opportunistic yeast infection produced by species of Candida in both pregnant and non-pregnant women were examined in this study. Lactococcus lactic (ATCC 11454)   extracted and chemical compounds identified by Gas Chromatography, the extract of L. lactic inhibited all Candida isolates in agar well diffusion assay and the inhibition  zone, it were (12, 11, 11, 11, 10 mm) for C. albicans, C. dublniesis, C. glabrata C. krusei and C. parapsilosis respectively, while minimum inhibiter concentration  were (64, 128, 128, 128, 128μg/ml) for C. albicans, C. dublniesis, C. glabrata C. krusei and C. parapsilosis respectively, the chemical compounds of  L. lactic unable inhibit efflux pump of all clinical Candida isolates after treated with (40, 20, 10, 5 mg/ml) of ethidium bromideOne hundred and fifty-four samples were collected from Bint Al-Huda Teaching Hospital in Thi-Qar Governorate divided to 104 women infected urinary tract infection (UTI) and 50 healthy women as control group. Vulvovaginal Candidiasis (VVC) is the most opportunistic yeast infection produced by species of Candida in both pregnant and non-pregnant women were examined in this study. Lactococcus lactic (ATCC 11454)   extracted and chemical compounds identified by Gas Chromatography, the extract of L. lactic inhibited all Candida isolates in agar well diffusion assay and the inhibition  zone,